2011
DOI: 10.1155/2011/518323
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Animal Models for Brucellosis Research

Abstract: Brucellosis is a chronic infectious disease caused by Brucella spp., a Gram-negative facultative intracellular pathogen that affects humans and animals, leading to significant impact on public health and animal industry. Human brucellosis is considered the most prevalent bacterial zoonosis in the world and is characterized by fever, weight loss, depression, hepato/splenomegaly, osteoarticular, and genital infections. Relevant aspects of Brucella pathogenesis have been intensively investigated in culture cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 80 publications
4
94
0
Order By: Relevance
“…It was also reported that BALB/c pregnant female mice infected with 10 6 cfu of B. abortus virulent strain 2308 developed a moderate multifocal necrotic placentitis associated with severe neutrophilic infiltrate and intralesional bacteria in trophoblastic cells (Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It was also reported that BALB/c pregnant female mice infected with 10 6 cfu of B. abortus virulent strain 2308 developed a moderate multifocal necrotic placentitis associated with severe neutrophilic infiltrate and intralesional bacteria in trophoblastic cells (Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…that affects humans as well as domestic and wild animals, with reproductive disorders as the main problem in domestic animals (Megid et al, 2010;Silva et al, 2011). The validly published species of Brucella are B. melitensis, B.…”
Section: Introductionmentioning
confidence: 99%
“…For this, clinical data and mostly laboratory in vivo models, in which different infection stages can be monitored, are essential. A widely used Brucella in vivo model is mouse, which largely recapitulates natural animal brucellosis (Silva et al 2011). Several Bartonella species also have a small animal model reflecting infection either (1) in the reservoir host (Fig.…”
Section: Lessons Learned From In Vivo Studiesmentioning
confidence: 99%
“…. It has a devastating impacts on public health, infecting around 500,000 new cases each year globally (Silva et al, 2011). The incidence of the disease is reported to be 2-8/ 1,000,000 in a global incidence report; however, according to World Organization for Animal Health (OIE) the incidence of brucellosis is 3.8 per million in the country (Saeed et al, 2014).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%